2020
DOI: 10.1111/iwj.13433
|View full text |Cite
|
Sign up to set email alerts
|

Fat grafting and platelet‐rich plasma for the treatment of diabetic foot ulcers: A feasibility‐randomised controlled trial

Abstract: Chronic, nonhealing diabetic foot ulcers (DFU) are increasing in prevalence and are often unresponsive to conventional therapy. Adipose tissue, containing adipose‐derived stem cells, and platelet rich plasma (PRP) are regenerative therapies rich in growth factors which may provide a solution to chronic wound healing. This study aimed to assess the feasibility of conducting a definitive randomised controlled trial (RCT) to investigate the efficacy of these therapies for the treatment of DFU. This was a single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 52 publications
0
56
0
Order By: Relevance
“…Concisely, a total of 716 studies were identified in the initial database search; 543 articles were excluded because they were not relevant to our study’s objective, according to our screening process outlined in Figure 1 . Among the 173 potentially relevant studies, 28 RCTs matched the inclusion criteria for the current meta-analysis [ 15 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. There were 146 studies further excluded: 106 studies were not RCTs, 19 studies did not use ASCT, 6 studies were non-human trials, 3 studies did not include lower extremity wounds, 4 studies used control groups that did not receive standard treatment with or without sham injections, and 8 studies were not retrievable full-length articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concisely, a total of 716 studies were identified in the initial database search; 543 articles were excluded because they were not relevant to our study’s objective, according to our screening process outlined in Figure 1 . Among the 173 potentially relevant studies, 28 RCTs matched the inclusion criteria for the current meta-analysis [ 15 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. There were 146 studies further excluded: 106 studies were not RCTs, 19 studies did not use ASCT, 6 studies were non-human trials, 3 studies did not include lower extremity wounds, 4 studies used control groups that did not receive standard treatment with or without sham injections, and 8 studies were not retrievable full-length articles.…”
Section: Resultsmentioning
confidence: 99%
“…With 304 patients treated with the ASCT and 323 patients assigned to the control groups, we investigated the effects of ASCT on the healing of LECWs ( Figure 2 A). Complete wound healing was defined as 100% re-epithelialization as judged by the treating podiatrist and clinician, with no need for further dressing therapy [ 47 ]. Overall, the results indicated that ASCT was associated with a significant increase in the complete wound healing rate as compared with that observed in the control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Potential favourable effects of leucocytes may be attributed to their roles in tissue remodelling, antibacterial affects, and regulation of immune responses 35 . Topical application or intradermal injection of PRP allow biomolecules to be delivered to target tissues, which effectively regulate some essential functions in the local microenvironment: proliferation, migration, and differentiation of stem cells (eg, dermal fibroblasts, epithelial cells, and endothelial cells), new collagen and matrix formation, modulation of inflammatory and immune responses, and angiogenesis, as well as antimicrobial effects 5,36‐40 . These healing and regenerative properties pave the way that PRP may be a potentially effective biomaterial in vitiligo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…35 Topical application or intradermal injection of PRP allow biomolecules to be delivered to target tissues, which effectively regulate some essential functions in the local microenvironment: proliferation, migration, and differentiation of stem cells (eg, dermal fibroblasts, epithelial cells, and endothelial cells), new collagen and matrix formation, modulation of inflammatory and immune responses, and angiogenesis, as well as antimicrobial effects. 5,[36][37][38][39][40] These healing and regenerative properties pave the way that PRP may be a potentially effective biomaterial in vitiligo treatment. Recently, some researchers have begun to combine PRP with several conventional treatments for vitiligo in comparison to monotherapy, but inconsistent results were reported.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective, human randomised single‐centre feasibility study was undertaken 39 . This was a three‐armed study comparing fat grafting, fat grafting with PRP, and routine care for the treatment of diabetic foot ulcers.…”
Section: Methodsmentioning
confidence: 99%